Interactive Knowledge Construction in Medical Problem-Based Learning: A Corpus-Based Study - Tokode, Olukayode Matthew; Dennick, Reg (Archives of Clinical and Biomedical Research, 2023)
Introduction: Due to methodological limitations, process-oriented studies have analyzed a group or fragments of problem-based learning (PBL) tutorial talk. Studies that examined several PBL tutorial talk and profile talk data into linguistic categories within a mixed methods analysis are scarce. The study aims to describe the knowledge construction processes of graduate entry medical students at Derby medical school PBL hybrid curriculum in the United Kingdom. Methods: A 253,145-word corpus was formed from the transcripts of 56 medical students and seven facilitators in seven tutorial groups. The frequent indicators of knowledge construction concepts were extracted using Wmatrix 3 programme. The concordance lines of the frequent indicators were analyzed thematically to define their functions. Results: The frequent indicators were verbal communication words (‘say’, ‘talk’, ‘point’ and ‘lecture’) and their inflexions, writing acts and visualization tools, coordinating and subordinating connectives and conversation interactional words (‘yes’/’yeah’ and ‘No’). The indicators were often used to mobilize prior knowledge and experience, report selfdirected study activities, regulate group interactional behaviours and construct knowledge. Conclusion: Corpus methodology allowed analysis of a larger dataset than before and provided an opportunity to describe how medical students used language to construct biomedical knowledge. The study findings contributed to the current research agenda of understanding the natural occurrences in the PBL tutorials and provided evidence of how medical students are being inducted into the professional practice of medicine. Future studies could link inter-mental verbal interactions with students’ achievement and evaluate misconceptions of biomedical knowledge.